Reactivity of a dititanium bis(pentalene) complex toward heteroallenes and main-group element–element bonds - Kilpatrick, A; Green, J; Cloke, F (American Chemical Society, 2016)
The reactivity of the Ti=Ti double bond in (μ,η 5 :η 5 -Pn † ) 2 Ti 2 (1; Pn † = 1,4-Si i Pr 3 2 C 8 H 4 ) toward isocyanide and heteroallene substrates, and molecules featuring homonuclear bonds between main-group elements (E-E) has bee n explored. Reaction of 1 with methyl isocyanide or 1,3-N,N′-di-p-tolylcarbodiimide resulted in the formation of the 1:1 adducts (μ,η 5 :η 5 -Pn † ) 2 Ti 2 (μ,η 2 -CNMe) (2) and (μ,η 5 :η 5 -Pn † ) 2 Ti 2 (μ-C{N(4-C 6 H 4 CH 3 )} 2 ) (3), respectively, which are thermally stable up to 100 °C in contrast to the analogous adducts formed with CO and CO 2 . Reaction of 1 with phenyl isocyanate afforded a paramagnetic complex, [(η 8 -Pn † )Ti] 2 (μ,κ 2 :κ 2 -O 2 CNPh) (4), in which the "double-sandwich" architecture of 1 has been broken and an unusual phenyl-carbonimidate ligand bridges two formally Ti(III) centers. Reaction of 1 with diphenyl dichalcogenides, Ph 2 E 2 (E = S, Se, Te), led to the series of Ti-Ti single-bonded complexes (μ,η 5 :η 5 -Pn † ) 2 [Ti(EPh)] 2 (E = S (5), Se (6), Te (7)), which can be considered the result of a 2e - redox reaction or a 1,2-addition across the Ti=Ti bond. Treatment of 1 with azobenzene or phenyl azide afforded [(η 8 -Pn † )Ti] 2 (μ-NPh) 2 (8), a bridging imido complex in which the pentalene ligands bind in an η 8 fashion to each formally Ti(IV) center, as the result of a 4e - redox reaction driven by the oxidative cleavage of the Ti=Ti double bond. The new complexes 2-8 were extensively characterized by various techniques including multinuclear NMR spectroscopy and single-crystal X-ray diffraction, and the experimental work was complemented by density functional theory (DFT) studies.